Nikah Sirri Menurut Hukum Islam Dan Hukum Positif - Zakaria, Endang; Saad, Muhammad (Kopertais Wilayah I DKI Jakarta dan Banten, 2021)
Islamic law defines marriage as an absolute obligation to follow Allah's command and carry it out as worship and represents a very strong bond. In the context of unregistered marriage, it can be defined as “a form of marriage based on religious law or custom, as well as one that is not announced to a crowd and is not registered with the marriage registry”. This paper discusses literacy in Islamic law and positive law on unregistered marriages. Positive law studies on unregistered marriages are carried out on the essence of the Law of the Republic of Indonesia and Government Regulations. According to Indonesian law, sirri marriage is a marriage that is not based on the principle of legality. In Islam, the study of unregistered marriage was based on Qur’an and hadith. This means that it is not legally binding. A marriage that is in accordance with the pillars and conditions of marriage is valid under Islamic law, as are marriages performed in sirri marriages, as defined in Indonesian law.